The Practical Conditions and Paths for Xinjiang to Integrate into the Upgraded Version of CPEC under the New Development Pattern (Journal of Interdisciplinary Insights, 2025)
As the flagship project of BRI in the post globalization era, CPEC has important strategic significance in responding to the profound changes unseen in a century and building a new development pattern. With the deepening of the joint construction of the Belt and Road, Xinjiang actively serves and integrates into the new development pattern, becoming a hub node for China to build a domestic and international dual cycle oriented to Europe and Asia. On the basis of explaining the achievements of the construction of CPEC, this paper focuses on the theme of high-quality development of the upgraded version of CPEC, analyzes the practical conditions for Xinjiang to integrate into the construction of the upgraded version of CPEC. From the perspectives of regional planning, industry integration, economic and trade cooperation, and knowledge sharing, it deeply discusses the paths for Xinjiang to integrate into the construction of the upgraded version of CPEC.
Keywords: New Development Pattern; Upgraded Version of CPEC; Practical Condition; Path